Aczonin, a 550-kD Putative Scaffolding Protein of Presynaptic Active Zones, Shares Homology Regions with Rim and Bassoon and Binds Profilin - Wang, Xiaolu; Kibschull, Mark; Laue, Michael M.; Lichte, Beate; Petrasch-Parwez, Elisabeth; Kilimann, Manfred W. (The Journal of cell biology, 1999)
Neurotransmitter exocytosis is restricted to the active zone, a specialized area of the presynaptic plasma membrane. We report the identification and initial characterization of aczonin, a neuron-specific 550-kD protein concentrated at the presynaptic active zone and associated with a detergent-resistant cytoskeletal subcellular fraction. Analysis of the amino acid sequences of chicken and mouse aczonin indicates an organization into multiple domains, including two pairs of Cys4zinc fingers, a polyproline tract, and a PDZ domain and two C2 domains near the COOH terminus. The second C2 domain is subject to differential splicing. Aczonin binds profilin, an actin-binding protein implicated in actin cytoskeletal dynamics. Large parts of aczonin, including the zinc finger, PDZ, and C2 domains, are homologous to Rim or to Bassoon, two other proteins concentrated in presynaptic active zones. We propose that aczonin is a scaffolding protein involved in the organization of the molecular architecture of synaptic active zones and in the orchestration of neurotransmitter vesicle trafficking.